Food and nutrition security under the public distribution system in Odisha - Bal Krishan; Seema Bathla (Agricultural Economics Research Review, 2023)
Odisha has been a frontrunner in overhauling its public distribution system (PDS), but its PDS has not contributed much to nutritional security. Over 60% of the state’s population is undernourished and malnourished, and the poor are more calorie-deficient despite having greater access to subsidized grain, although there has been an upturn in both the coverage and the outreach of PDS, devoid of rural– urban bias. It is recommended that the Government of Odisha improves coverage by instituting a statewide, universal system and widening the food basket to include high-protein pulses, coarse cereals, and biofortified food.